Multi-omics analysis reveals distinct non-reversion mechanisms of PARPi resistance in BRCA1- versus BRCA2-deficient mammary tumors - Bhin, Jinhyuk; Paes Dias, Mariana; Gogola, Ewa; Rolfs, Frank; Piersma, Sander R.; de Bruijn, Roebi; de Ruiter, Julian R.; van den Broek, Bram; Duarte, Alexandra A.; Sol, Wendy; van der Heijden, Ingrid; Andronikou, Christina; et al. (Cell reports (Cambridge), 2023)
BRCA1 and BRCA2 both function in DNA double-strand break repair by homologous recombination (HR). Due to their HR defect, BRCA1/2-deficient cancers are sensitive to poly(ADP-ribose) polymerase inhibitors (PARPis), but they eventually acquire resistance. Preclinical studies yielded several PARPi resistance mechanisms that do not involve BRCA1/2 reactivation, but their relevance in the clinic remains elusive. To investigate which BRCA1/2-independent mechanisms drive spontaneous resistance in vivo, we combine molecular profiling with functional analysis of HR of matched PARPi-naive and PARPi-resistant mouse mammary tumors harboring large intragenic deletions that prevent reactivation of BRCA1/2. We observe restoration of HR in 62% of PARPi-resistant BRCA1-deficient tumors but none in the PARPi-resistant BRCA2-deficient tumors. Moreover, we find that 53BP1 loss is the prevalent resistance mechanism in HR-proficient BRCA1-deficient tumors, whereas resistance in BRCA2-deficient tumors is mainly induced by PARG loss. Furthermore, combined multi-omics analysis identifies additional genes and pathways potentially involved in modulating PARPi response. [Display omitted] •HR recovery drives PARPi resistance in BRCA1-KO tumors but not in BRCA2-KO tumors•HR recovery in PARPi-resistant BRCA1-KO tumors occurs mostly via 53BP1 loss•HR-deficient PARPi-resistant BRCA1-KO tumors show increased immune infiltration•PARG loss is the most common alteration in PARPi-resistant BRCA2-deficient tumors Bhin et al. use multi-omics and HR analysis of matched treatment-naive and PARPi-resistant BRCA1/2-KO mouse tumors to investigate non-reversion mechanisms driving spontaneous resistance in vivo. HR restoration via 53BP1 loss and restoration of PARP signaling via PARG loss are the two dominant resistance mechanisms in BRCA1-KO and BRCA2-KO tumors, respectively.